Digitalization and Sustainable Manufacturing : Twin Transition in Norway - Sverre Gulbrandsen-Dahl; Heidi C. Dreyer; Einar L. Hinrichsen; Halvor Holtskog; Kristian Martinsen; Håkon Raabe; Gabor Sziebig (Routledge, 2025)
The manufacturing industry is facing massive changes driven by digitalization and sustainability. It is being redefined to meet the UN SDGs with the creation of new materials, processes and machinery. The drive for digitalization in order to use resources more effectively and efficiently adds to the complexity of this twin transition. This book presents results from 8 years of research with 15 industry partners, following the transition towards a digitalized industry 4.0 manufacturing and sustainable manufacturing paradigm.The selected chapters demonstrate how globally competitive manufacturing in high-cost countries such as Norway is enabled by AI-supported intelligent and flexible automation and the use of digital twins, as well as human-centred manufacturing. This book describes the interactions in innovative and sustainable organizations and changes in materials, products and processes, digital twins and AI-supported automated manufacturing processes. Supported by case studies and reflections from the manufacturing industry, this book evaluates how the combination of digitalization and sustainability enables competitiveness. With a focus on multi-material products and processes, robust and flexible automation and innovative and sustainable organizations, it provides a multi-disciplinary insight into the challenges and opportunities faced by manufacturing industries over time.This book serves as an ideal reference for researchers, scholars and policymakers in manufacturing, production and operations, with a particular interest in technology and sustainability.